Correlations of Ecological Trends in Post-Socialist European Countries, 1993–2023 - Lakócai, Csaba (Studia Historiae Oeconomicae, 2025)
During the 2025 conference of the World Economic History Congress (WEHC) in Lund, Sweden, Csaba Lakócai, post-doctoral researcher at the University of Ostrava, presented his research topic in the session “Equalities and Sustainability Challenges in Transition Economies in Central and Eastern Europe after 1989”. The research topic has been produced with the financial support of the European Union under the REFRESH – Research Excellence For REgion Sustainability and High-tech Industries project number CZ.10.03.01/00/22_003/0000048 via the Operational Programme Just Transition.